Pemerintahan Elektronik dan Transformasi Digital Menuju Birokrasi Kelas Dunia di Badan Kepegawaian Provinsi Bali - Pande Putu Anugraha Dewata; I Gusti Ayu Agung Dewi Sucitawathi Pinatih (Jurnal Bina Praja, 2025)
Digital transformation through e-government policy has become a strategic agenda of the Indonesian government in realizing effective, efficient, transparent, and accountable governance. One form of e-government implementation in the personnel sector is the utilization of the Personnel Management Information System (SIMPEG) developed by the Bali Province Personnel and Human Resources Development Agency (BKPSDM/HR). Although it has been implemented systematically, the implementation of SIMPEG still faces various challenges, especially related to system integration, data updating, and human resource readiness. This study aims to analyze the implementation of e-government policy through SIMPEG in BKPSDM Bali Province, as well as to identify supporting and inhibiting factors in its implementation. The study uses a qualitative descriptive approach with data collection techniques in the form of observation, in-depth interviews, and documentation studies. Research informants were determined purposively, including the leaders and main managers of SIMPEG. Data analysis was carried out using the Miles, Huberman, and Saldaña model through the stages of data reduction, data presentation, and conclusion drawing. The results show that the implementation of e-government through SIMPEG has been running with the support of regulations, infrastructure, and strong leadership commitment, but is still at the interaction and transaction stage and has not achieved integrated digital bureaucratic transformation. The main problems encountered include fragmented system governance, limited interoperability with the central personnel system, the digital literacy gap among civil servants, and resistance to changes in work culture. These findings confirm that the success of e-government is determined not only by technological readiness, but also by organizational and human resource factors. This research provides conceptual and practical contributions in strengthening e-government implementation in the public sector, particularly in encouraging data-driven and sustainable digital transformation of personnel.